A new modified Fuzzy S-VIKOR method for best alternative selection - et. al., Shweta Raval, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
VIKOR is a broadly utilized MCDM method for positioning the attainable other options and choosing the best one. Most of the researchers are used L^1 - norm for calculating utility measure in the VIKOR method. In this research work, a similarity measure is used to modify the VIKOR method. Triangular fuzzy numbers are used in this modified S-VIKOR method to represent the criteria values. The reason of this work was to create modern alteration in VIKOR to avoid complications while solving for enormous numbers of information and non-common criteria. Three different similarity measures are used in this work and also trying to find out the best possible similarity measure for this method. Furthermore, a case study of faculty evaluation for the set of criteria is presented to explain the new method, and comparison is also carried out to show the benefits of this work.